Mandibular First Premolar with Three Roots: A Case Report - kakkar, pooja; Singh, Anant (Iranian Endodontic Journal, 2012)
Anatomy of the root canal system always effects endodontic treatment outcome. Mandibular premolar teeth show extreme variations in root canal morphology. First premolars usually exhibit basic one root and one canal anatomy. The occurrence of three roots in mandibular first premolar has not been commonly reported in literature. This article reports a case of successful nonsurgical endodontic management of mandibular first premolar with three canals and three different apical foramina.